Combined resistance training with aerobic training improves physical performance in patients with coronary artery disease: A secondary analysis of a randomized controlled clinical trial - Kambic, Tim; Šarabon, Nejc; Lainscak, Mitja; Hadžić, Vedran (Frontiers in Cardiovascular Medicine, 2022)
BBackground The efficacy of combined of resistance training (RT) and aerobic training (AT) compared with AT alone is well established in cardiac rehabilitation (CR); however, it remains to be elucidated whether RT load (high-load [HL] vs. low-load [LL]) modifies the outcomes. The aim of our study was to investigate the effects of HL-RT and LL-RT combined with AT in comparison to AT alone on body composition and physical performance in patients with coronary artery disease (CAD) enrolled in phase II CR. Methods We randomised seventy-nine patients with a stable CAD to 12 weeks of lower limb LL-RT+AT (35%-40% of one repetition maximum [1-RM]; n = 28), HL-RT+AT (70 %-80% of 1-RM; n = 26) or AT (n = 25). Fifty-nine patients (75 % males) with mean (standard deviation) age 61 (8) years and left ventricular ejection fraction 53 (9) % completed LL-RT (n = 19), HL-RT (n = 21) and AT (n = 19). Body composition and physical performance (upper and lower submaximal muscle strength, flexibility, balance and mobility) were measured at baseline and post-training. Results Training intervention had no significant impact on time x group interaction in the body composition measures. There was a significant time x group interaction for the gait speed test, chair sit-and-reach test, arm curl test, Stork balance test, Up-and-Go test, STS-5 and 6-min walk distance (p-values ≤ 0.001-0.04) following the training intervention. After the training intervention, HL-RT improved gait speed (+12 %, p =0.044), arm curl (+13 %, p = 0.037) and time of Up-and-go test (+9 %, p <0.001) to a greater extent compared with AT group, while there was a greater improvement in time of Up-and-Go test (+18 %, p < 0.001) and time of five sit-to-stands (+14 %, p = 0.016) following LL-RT when compared with AT. There were no differences between HL-RT and LL-RT in post-training improvement in any of the physical performance measures. Conclusion The combination of AT with HL-RT or LL-RT promoted similar improvements in physical performance, which were superior to AT. Therefore, both types of combined AT and RT can be applied for patients with CAD.